KAJIAN EFISIENSI ALOKASI PENGGUNAAN INPUT PADA USAHA TERNAK AYAM RAS PETELUR - Kustiawati Ningsih (Universitas Sebelas Maret, 2014)
The research wasconducted inJune-July 2013 at Bettet Village Pamekasan City Subdistrict Pamekasan Regency. The research objectivewas to determine the allocation efficiency of input use on breeding laying hens. Secondary and primary data were obtained through interview and observation methods. Descriptive analysis with applying the Cobb-Douglas production function and testing Efficiency Value Price for Input Use (Factor) is used to analyze the data. Results showed that the model of Cobb Douglas production function breeding laying hens at Bettet Village Pamekasan City Subdistrict Pamekasan Regenc yis quite good. This can be seen in the value ofR2=0.9585, meaning that the independent variable(X1 s/dX6) in the modelis able to explain the relationship with the dependent variable (production) of 95.85%,while the remaining 4.15% is explained by other variables not in the study. In addition, the results of the Cobb Douglas production function model breeding laying hens at Bettet Village have calculated F value = 527.485 > F table = 2.599 with =0.05 and degrees of freedom df(6,20), meaning that the independent variables(X1 s/dX6) together in a model that explains the relationship of the dependent variable (production) significantly. Assessment results for the efficiency of use of each input prices (factor) indicates that the allocation of the inputs on breeding laying hens at Bettet Village Pamekasan City Subdistrict Pamekasan Regency still not efficient. It can be seen from the t value of each input is greater thanttable with α=0.05and19 degrees of freedom (df =19).